Introduction to philosophy : classical and contemporary readings - Bratman, Michael; Perry, John (Oxford University Press, 1999)
This is the third edition of Perry and Bratman's highly successful anthology intended for the introduction to philosophy course. It is the most comprehensive topically organized anthology of classical and contemporary philosophy available. The collection is perceived as one of the more serious and challenging introductions available. It includes sections on the meaning of life, God and evil, epistemology, philosohy of science, the mind/body problem, freedom of will, consciousness, ethics, and philosophical puzzles. The third edition includes the following new selections: Plato: Apology; Nelson Pike: Hume on Evil; J.L. Mackie: Evil and Omnipotence; Elizabeth Anderson: Knowledge, Human Interests, and Objectivity in Feminist Epistemology; David Lewis: Mad Pan and Martian Pain; Hilary Putnam: Turning Machines; Frank Jackson: What Mary Didn't Know; David Lewis: Knowing What It's Like; John Perry: Dialogue Concerning Personal Identiy and Immortality; Peter Strawson: Freedom and Resentment; Rosalind Hursthouse: Virtue Theory and Abortion; G.A. Cohen: Where the Action Is - On the Site of Distributive Justice; Samuel Scheffler: Responsibility, Reactive Attitudes and Liberalism; Debra Satz: Markets in Women's Reproductive Labor; Kwame Anthony Appiah: Racisms; Kavka's Toxin Puzzle; Quinn's Puzzle of the Self-Torturer.